A Robust, Broadly Absorbing Fulgide Derivative as a Universal Chemical Actinometer for the UV to NIR Region. Issue 6 (18th April 2019) - Reinfelds, Matiss; Hermanns, Volker; Halbritter, Thomas; Wachtveitl, Josef; Braun, Markus; Slanina, Tomáš; Heckel, Alexander
Abstract: A fulgide photoswitch is presented as a novel actinometer for a broad range of wavelengths from the UV to the NIR region (340–700 nm). It is easily accessible and has a robust photochemistry and high fatigue resistance. Its photophysics and photochemistry are described in detail. Quantum yields of photoswitching were measured for a series of wavelengths and standardized against known standards (ferrioxalate actinometry, calibrated photodiode). We also present a method for the precise determination of photoswitching quantum yields by global analysis of the whole spectra and an alternative quick and easy method for rapid determination of photon fluxes. Abstract : Counting photons in the red : Indolyl‐fulgide photoswitching is established as a novel actinometric method for determination of photon fluxes between 340–700 nm. Facile synthesis, simple handling and straightforward analytical readout and analysis make this technique superior to other known actinometers in this region.